The Impact of the European Convention on Human Rights on Private International Law - Kiestra, Louwrens R. author. aut Link
XI, 329 p.
Keywords: The focus of the present book is the impact of the European Convention on Human Rights (ECHR) on the three main topics of private international law (PIL): jurisdiction, applicable law, and the recognition and enforcement of foreign judgments. The author sets off with a discussion whether the ECHR is at all applicable to issues of PIL and the relationship between Article 1 of the Convention and PIL. He then examines the case law of the European Court of Human Rights and selected national courts and by doing so thoroughly maps the interaction between PIL and the rights guaranteed in the ECHR. On this wealth of information the author bases his final conclusions. Next to a list of cases consulted and a comprehensive bibliography, the book offers brief introductions to PIL and the ECHR for readers who are less familiar with either of the topics. This makes the book not only a valuable tool for specialists and practitioners in the fields covered, but at the same time a well-documented basis for students and starting researchers specializing in either or both directions. Louwrens Kiestra presently works for the District Court Limburg, The Netherlands.